2011
DOI: 10.1029/2011jc007371
|View full text |Cite
|
Sign up to set email alerts
|

Airborne surveys of snow depth over Arctic sea ice

Abstract: [1] During the spring of 2009, an ultrawideband microwave radar was deployed as part of Operation IceBridge to provide the first cross-basin surveys of snow thickness over Arctic sea ice. In this paper, we analyze data from three ∼2000 km transects to examine detection issues, the limitations of the current instrument, and the regional variability of the retrieved snow depth. Snow depth is the vertical distance between the air-snow and snow-ice interfaces detected in the radar echograms. Under ideal conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
114
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(120 citation statements)
references
References 14 publications
6
114
0
Order By: Relevance
“…Methods for the retrieval of snow depth from FMCW radar operation over sea ice have been described in previous studies (e.g., Galin et al, 2011;Kwok et al, 2011). Retrieval methods for the IceBridge snow radar have been described by Farrell et al (2012).…”
Section: Snow Depth Retrievalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Methods for the retrieval of snow depth from FMCW radar operation over sea ice have been described in previous studies (e.g., Galin et al, 2011;Kwok et al, 2011). Retrieval methods for the IceBridge snow radar have been described by Farrell et al (2012).…”
Section: Snow Depth Retrievalsmentioning
confidence: 99%
“…This influences the comparison in two ways: (1) it leads to errors in the vertical range compensation, which are used to account for changes in the aircraft altitude and (2) it introduces a 5-20 m offset between the geolocations of the snow radar and ATM. While we expect that averaging to a 40 m length scale reduces the problem of geolocation errors of this magnitude for sea ice thickness retrievals using the radar and ATM freeboard data, it nonetheless is a source of error if one seeks to carry out a one-to-one matching of the ATM data over the snow radar footprint such as done by Kwok et al (2011). Aircraft pitch and roll introduces errors in the aircraft altitude correction that results in residual features in the vertical dimension of the radar data when they are compared to the ATM elevation data that have been corrected for aircraft pitch and roll.…”
Section: Snow Depth Retrievalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The snow data as used in ICESat (Kwok and Cunningham, 2008) are derived from reanalysis data and satellite retrieved sea ice motion, while the climatological snow depth data in Warren et al (1999) as used by CryoSat-2 (Laxon et al, 2013) contain large uncertainty due to interpolation and interannual variability and may not be adequate for the present day under the context of climate change (Kwok et al, 2011;Webster et al, 2014). The retrieval of snow depth with passive microwave satellite remote sensing has been carried out in various studies.…”
mentioning
confidence: 99%
“…Besides, with the better penetration of L-band signal in the sea ice cover, it is also demonstrated that there is retrievability of thin sea ice thickness with L-band data, as in Kaleschke et al (2010) and Tian-Kunze et al (2014). Although airborne remote sensing methods have limited spatial and temporal coverage, campaigns such as NASA's Operation IceBridge (OIB) carry out high-resolution scanning of the sea ice cover (Kwok et al, 2011;Kurtz et al, 2013;Brucker and Markus, 2013) and provide invaluable data that are organized into flight-track-based segments of the sea ice cover.…”
mentioning
confidence: 99%